Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 6 - Inverse Functions - 6.3* The Natural Exponential Function - 6.3* Exercises - Page 455: 107


$b^{x-y}=\frac{b^{x}}{b^{y}}$; Second Law of Exponents

Work Step by Step

We already know that $b^{x}=e^{xlnb}$ Now, $b^{x-y}=e^{(x-y)lnb}$ This implies $b^{x-y}=e^{xlnb-ylnb}=\frac{e^{xlnb}}{e^{ylnb}}$ Hence, $b^{x-y}=\frac{b^{x}}{b^{y}}$ This is known as second Law of Exponents; where x and y are real numbers.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.